1981
DOI: 10.1007/bf00119926
|View full text |Cite
|
Sign up to set email alerts
|

Pressure and humidity effects on optical refractive-index fluctuations

Abstract: Although temperature fluctuations dominate the variance of optical refractive index fluctuations it has been shown recently that humidity fluctuations can also be important (e.g., Friehe etal., 1975). This paper reports on simultaneous measurements of temperature, humidity and pressure so that the relative importance of all three can be investigated. For the dry site where the measurements were made, the humidity contribution was less than other investigators had found. The major contribution of the pressure f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…They also gathered quantitative evidence of the extended and multiple transitions characteristic of non-ideal conditions. Such observations were consistent with the aerosol dependencies studied by McBean and Elliott (1981) and Sadot and Kopelka (1992).…”
Section: Introductionsupporting
confidence: 91%
“…They also gathered quantitative evidence of the extended and multiple transitions characteristic of non-ideal conditions. Such observations were consistent with the aerosol dependencies studied by McBean and Elliott (1981) and Sadot and Kopelka (1992).…”
Section: Introductionsupporting
confidence: 91%
“…Priestley and Hill (1985) measured six positive and six negative t-q cospectra at BAO that behaved as f -513 . McBean and Elliott (1981) and Kohsiek (1982), however, did not find the predicted inertial-convective subrange behavior in the t-q cospectra that they obtained over dry land. Figure 13 α is thus important confirmation of the existence of an f-5/3 inertial-convective subrange in negative t-q cospectra.…”
Section: T-q Cospectramentioning
confidence: 82%
“…The temperature spectrum always contributed at least 96% to the 0.55-µ m CA value, so I have not provided a similar breakdown for this wavelength in Table 4. McBean and Elliott (1981) also found that temperature fluctuations far outweighed other contributions to C^, in the visible region over land. Over the ocean, on the other hand, Antonia et al (1978) reported that the t-q contribution to CA could be 5-10% even though the q contribution was less than 1%.…”
Section: Refractive Index Spectramentioning
confidence: 86%
“…On the other hand, some of the observations claiming a deviation from f -5/3 may be explained by sensor separation. McBean and Elliott (1981) who used a 50 cm sensor separation, found a too rapid drop-off of the cospectrum for frequencies above 1 Hz. They do not give wind speeds, but assuming a value of 211 m s-', this corresponds to wavenumbers zz= 1 m-', which compares well with our estimate 0.3 6 -' = 0.6 m-'.…”
Section: Discussionmentioning
confidence: 99%